INTERSECTIONAL OPPRESSIONS THROUGH LANGUAGE: CASE STUDIES IN RACE, GENDER AND CLASS IN TO KILL A MOCKINGBIRD AND MY FAIR LADY - Berchez, Amanda [UNESP]; Manoel, Gabriel Gandini; Rezende, Paulo Ricardo Passos (Univ Estado Mato Grosso, 2024)
This study aims to investigate the impact of many dimensions on language use in Harper Lee's To kill a mockingbird and George Cukor's My fair lady . Regarding the first one, we distinctly focus on racially charged terminology, further exploring gender and class biases portrayed in the second one. Our methodology involves in-depth discourse analysis and critical examination of linguistic nuances, societal implications and narrative contexts within the works. The main hypothesis is that language acts as both a reflection and a catalyst for societal norms, playing a pivotal role in shaping perceptions, either for inclusivity or exclusion within specific communities.
Keywords: language; discourse; Harper Lee's To kill a mockingbird; My fair lady